Overweight and obesity and the health of populations of PALOP - Rosado-Marques, Vitor (2016)
The prevalence of overweight and obesity continues to increase globally, particularly obesity. This increase is more pronounced in countries with lower income, putting the health systems of these countries, already quite weak, at risk. The data available for the Portuguese-speaking African countries (PALOP), in addition to being scarce, show an enormous diversity, which may be related to different methodologies of collection. Even so, it allows the observation that the situation is, in general, quite worrying and that for women the values are very high. Knowing the strong association between overweight/obesity and non-communicable diseases (NCDs), there should be a special attention of the health authorities to this problem. NCDs are becoming increasingly frequent in Africa and in sub-Saharan Africa, where communicable diseases and undernutrition still predominate, already accounting for 25% of deaths. The incidence and prevalence of overweight/obesity and NCDs in the PALOP are not yet fully identified, so an investment in research that will allow the implementation of actions to prevent and control excess weight, particularly in childhood, is necessary along with other actions aimed at combating existing nutritional problems in these countries.